Merocyanine/C60 planar heterojunction solar cells: effect of dye orientation on exciton dissociation and solar cell performance - Ojala, Antti; Lovrinčić, Robert; Poelking, Carl; Trollmann, Jens; Pucci, Annemarie (Advanced functional materials, 2012)
In this study the charge dissociation at the donor/acceptor heterointerface of thermally evaporated planar heterojunction merocyanine/C60 organic solar cells is investigated. Deposition of the donor material on a heated substrate as well as post-annealing of the complete devices at temperatures above the glass transition temperature of the donor material results in a twofold increase of the fill factor. An analytical model employing an electric-field-dependent exciton dissociation mechanism reveals that geminate recombination is limiting the performance of as-deposited cells. Fourier-transform infrared ellipsometry shows that, at temperatures above the glass transition temperature of the donor material, the orientation of the dye molecules in the donor films undergoes changes upon annealing. Based on this finding, the influence of the dye molecules’ orientations on the charge-transfer state energies is calculated by quantum mechanical/molecular mechanics methods. The results of these detailed studies provide new insight into the exciton dissociation process in organic photovoltaic devices, and thus valuable guidelines for designing new donor materials.